Board Characteristics and Tax Avoidance: The Mediating Role of Integrated Reporting Quality - Dwi ramadhan, Sandicha; Saputra, Dian; Nawas, Abrar; Abdul Rahman, Firdaus (Universitas Muhammadiyah Prof. DR HAMKA., 2023)
This study examines the nexus between female directors, independent commissioners, board size, political connections, and Corporate Tax Avoidance (CTA) within the non-cyclical consumer goods sector of the Indonesian Stock Exchange (IDX) from 2019 to 2022. The research also tests the mediating influence of Integrated Reporting Quality (IR), addressing the significance of Integrated Reporting in Indonesia. Using SmartPLS 3 and PLS-SEM, the findings reveal that female directors are negatively associated with Tax Avoidance, while board size has a positive effect, and independent commissioners and political connections show insignificant impacts. The mediating role of IR Quality indicates that improved reporting quality reduces tax avoidance in relation to board characteristics and political connections. The study underscores the importance of IR quality in enhancing corporate transparency and reducing fraudulent activities, advocating for the adoption of Integrated Reporting frameworks by both government bodies and companies.